2021
DOI: 10.3758/s13421-021-01249-z
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for item-level variance in recognition memory: Comparing word frequency and contextual diversity

Abstract: Contextual diversity modifies word frequency by ignoring the repetition of words in context (Adelman, Brown, & Quesada, 2006, Psychological Science, 17(9), 814-823). Semantic diversity modifies contextual diversity by taking into account the uniqueness of the contexts that a word occurs in when calculating lexical strength (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 102 publications
4
20
0
Order By: Relevance
“…Previous studies have demonstrated the superiority of contextual diversity measures of lexical strength over the classic word frequency measure (Adelman et al, 2006; Johns, 2021a, 2021c; Johns et al, 2020). The goal of this study was to determine if these findings extend to multiword expressions, through the analysis of idiom familiarity values from Libben and Titone (2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the superiority of contextual diversity measures of lexical strength over the classic word frequency measure (Adelman et al, 2006; Johns, 2021a, 2021c; Johns et al, 2020). The goal of this study was to determine if these findings extend to multiword expressions, through the analysis of idiom familiarity values from Libben and Titone (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Johns (2021a) has recently demonstrated that the advantage of discourse and user contextual diversity measures generalizes to accounting for word-level recognition memory rates, while Johns (2021c) showed that a distributional model trained with the communication patterns of users on Reddit allowed for a unique signal of word meaning to be constructed. For example, distributional models trained with word-based contextual representations appeared to extract subordinate semantic category members as nearest neighbors of a word (e.g., different dog breeds for poodle , different sports for basketball ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This follows previous work by Thompson et al (2020) examining the relativity of word meanings across languages. To accomplish this, 500 corpora of prominent users on the internet forum Reddit were constructed, following recent work using Reddit to examine distributional properties of words in a communicative environment to examine lexical organization and lexical semantics (Johns, 2021a(Johns, ,b, 2022. A count-based distributional framework (first described in and further explored by Johns, 2021b), which integrates training procedures from neural embedding models, was used to derive semantic representations for words from the user corpora.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, here individual user corpora will be formed from high-level commenters on the internet forum Reddit. This language source has recently been used to examine communicative and socially-based effects in lexical organization (Johns, 2021a(Johns, , 2022Senaldi, Titone, & Johns, 2022) and lexical semantics (Johns, 2021b) using distributional semantic modeling.…”
Section: Models Of Semantic Memorymentioning
confidence: 99%